Status of climacteric symptoms among middle-aged to elderly Japanese women: Comparison of general healthy women with women presenting at a menopausal clinic - Ikeda, Toshiyuki; Makita, Kazuya; Ishitani, Ken; Takamatsu, Kiyoshi; Horiguchi, Fumi; Nozawa, Shiro (The Journal of obstetrics and gynaecology research, 2005)
Aim: To examine the status and characteristics of climacteric symptoms reported by generally healthy middle‐aged to elderly women in Japan, those living in Saitama Prefecture were surveyed . Methods: The subjects comprised 398 women ranging in age from 40 to <60 years (mean age, 50.5 years). Climacteric symptoms were objectively assessed using the Keio questionnaire. The total scores obtained for the 40 symptoms were used to calculate symptom prevalence and severity. Results: (i) The most frequent symptom was poor memory, reported by 88.7% of the women. (ii) Lumbar‐sacral back pain was rated as a severe symptom by the highest percentage of women (15.3%). (iii) The prevalence and severity of poor memory and lumbar‐sacral back pain did not differ with menopausal status. (iv) Hot flashes and sweats were slightly higher in peri‐ and early postmenopausal women than in premenopausal women. Conclusions: The present study showed that healthy women who do not consult physicians because of climacteric symptoms are primarily concerned with age‐related symptoms, such as poor memory, loss of hair, and forgetfulness.